A novel tryptophan-derived alkaloid and other constituents from Guettarda speciosa (Rubiaceae: Cinchonoideae–Guettardeae). (April 2021) - Muangrom, Wanitcha; Bacher, Markus; Berger, Andreas; Valant-Vetschera, Karin; Vajrodaya, Srunya; Schinnerl, Johann
Abstract: Phytochemical examination of two Thai accessions of the widespread paleotropical Guettarda speciosa (Rubiaceae: Cinchonoideae–Guettardeae) led to the isolation of the hitherto undescribed tryptophan-derived alkaloid 5α-carboxystrictosidinic acid together with 5α-carboxystrictosidine, the iridoid glucoside loganic acid and 5- O -caffeoylquinic acid from the root bark extract. The leaf extract further yielded 3- O -caffeoylquinic acid and 4, 5-di- O -caffeoylquinic acid. The structures of the isolated compounds were established by NMR and MS techniques and compared to other species of Guettarda . In addition, the structural differentiation of alkaloids within this genus is discussed with special emphasis on 5α-carboxy derivatives suggesting a pathway apart from the strictosidine biosynthetic route. Graphical abstract: Image 1 Highlights: Thai accessions from Guettarda speciosa were studied for the first time. The novel alkaloid 5α-carboxystrictosidinic acid is described. Chlorogenic acids are reported from Guettarda speciosa for the first time.